The Structure and Flexural Properties of Typha Leaves - Jingjing Liu; Zhihui Zhang; Zhenglei Yu; Yunhong Liang; Xiujuan Li; Luquan Ren (Applied Bionics and Biomechanics)
The Typha leaf has a structure of lightweight cantilever beam, exhibiting excellent mechanical properties with low density. Especially, the leaf blade evolved high strength and low density with high porosity. In this paper, the structure of Typha leaf was characterized by microcomputed tomography (Micro-CT) and scanning electron microscopy (SEM), and the relationship with flexural properties was analyzed. The three-point bending test was performed on leaves to examine flexural properties, which indicated that the flexural properties vary from the base to the apex in gradient. The cross-sectional geometry shape of the leaf blade presented a strong influence on the optimized flexural stiffness. The load carrying capacity of the leaf depended on the development level of the epidermal tissue, the vascular bundle, the mechanical tissue, and the geometric properties. The investigation can be the basis for lightweight structure design and the application in the bionic engineering field.